A method for preparing a negative electrode sheet, a negative electrode sheet and a lithium ion battery

By combining silicon-carbon materials of different shapes into a double-layer structure and setting arc grooves on the negative electrode current collector, the problem of insufficient peel strength of silicon-carbon negative electrode materials during battery charging and discharging is solved, and a negative electrode sheet with high peel strength and capacity and rate performance is achieved.

CN119560510BActive Publication Date: 2025-05-02SUZHOU QINGTAO NEW ENERGY TECH CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202510132884.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-02-06
Publication Date
2025-05-02
Estimated Expiration
2045-02-06

AI Technical Summary

Technical Problem

The existing silicon carbon negative electrode materials are prone to volume expansion stress during the charging and discharging of the battery, resulting in insufficient peeling strength from the negative electrode current collector, affecting the internal resistance, capacity and service life of the battery.

Method used

By combining silicon-carbon negative electrode materials of different shapes and designing them into a double-layer structure, combined with the design of arc-shaped grooves, the contact area between spherical or spherical silicon-carbon particles and the negative electrode current collector is increased, and the peel strength is improved.

Benefits of technology

It achieves a negative electrode plate with high peel strength, with capacity and rate performance, extending the service life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_19
    Figure SMS_19
Patent Text Reader

Abstract

The present invention provides a method for preparing a negative electrode sheet, a negative electrode sheet and a lithium-ion battery. The preparation method comprises: preparing a negative electrode current collector, a first active material layer slurry and a second active material layer slurry; coating the second active material layer slurry on the negative electrode current collector to form a second active material layer; coating the first active material layer slurry on the second active material layer to form a first active material layer to obtain a negative electrode sheet to be processed; drying the negative electrode sheet to be processed to form a negative electrode sheet; wherein an arc-shaped groove is provided on the negative electrode current collector, the first active material layer slurry comprises block silicon carbon, the second active material layer slurry comprises spherical or quasi-spherical silicon carbon particles, and the spherical or quasi-spherical silicon carbon particles are at least partially arranged in the arc-shaped groove. The present invention obtains a negative electrode sheet with high peeling strength and both capacity performance and rate performance by compounding silicon-carbon materials of different shapes and designing them into a double-layer structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of batteries, and in particular relates to a method for preparing a negative electrode sheet, a negative electrode sheet and a lithium ion battery. Background Art

[0002] At present, the negative electrode material of rechargeable batteries is the carrier of metal ions and electrons during the charging process of the battery, and plays an important role in the storage and release of energy. With the demand for higher energy density in new energy vehicles and consumer lithium-ion batteries, higher requirements are also placed on the capacity of negative electrode materials. Silicon-based negative electrodes are regarded as one of the ideal choices for the next generation of high energy density secondary batteries due to their high theoretical specific capacity.

[0003] Silicon-carbon materials have been intensively studied as commonly used silicon-based negative electrode materials. However, during the battery charging and discharging process, silicon-carbon materials will produce large volume expansion stress, causing them to easily fall off the negative electrode current collector, thereby increasing the internal resistance of the battery and affecting the battery capacity and service life.

[0004] Therefore, how to enhance the peeling strength between the negative electrode material and the negative electrode current collector while making the lithium-ion battery have both capacity performance and rate performance is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a negative electrode sheet, a negative electrode sheet and a lithium-ion battery. The present invention compounds silicon-carbon negative electrode materials of different shapes and designs the above materials into a double-layer structure, thereby obtaining a negative electrode sheet with high peel strength and both capacity performance and rate performance.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a method for preparing a negative electrode sheet, comprising:

[0008] S1. Preparing a negative electrode current collector, a first active material layer slurry and a second active material layer slurry;

[0009] S2. The second active material layer slurry is coated on the negative electrode current collector to form a second active material layer;

[0010] S3. coating the first active material layer slurry on the second active material layer to form a first active material layer to obtain a negative electrode sheet to be processed;

[0011] S4. The negative electrode sheet to be treated is dried to form a negative electrode sheet;

[0012] The negative electrode current collector is provided with an arc-shaped groove, the first active material layer slurry includes block silicon carbon, the second active material layer slurry includes spherical or quasi-spherical silicon carbon particles, and the spherical or quasi-spherical silicon carbon particles are at least partially arranged in the arc-shaped groove.

[0013] Preferably, the maximum depth of the arc-shaped groove is d, the opening diameter of the arc-shaped groove is D, the average particle size of the spherical or quasi-spherical silicon-carbon particles is D50, and the thickness of the negative electrode current collector is h, satisfying the following relationship: , where 0<D≤D50, d<h / 2, α is the coefficient, 1≤α≤2.2.

[0014] Preferably, the first active material layer slurry further includes fast-filling graphite, and the total mass of the blocky silicon carbon and the fast-filling graphite accounts for 92.6% to 96.1% of the mass of the first active material layer.

[0015] Preferably, the second active material layer slurry further includes high-capacity graphite, and the total mass of the spherical or quasi-spherical silicon-carbon particles and the high-capacity graphite accounts for 89.4% to 95.6% of the mass of the second active material layer.

[0016] Preferably, the mass ratio of the block silicon carbon to the fast-filling graphite is 3:97 to 95:5.

[0017] Preferably, the mass ratio of the spherical or quasi-spherical silicon-carbon particles to the high-capacity graphite is 3:97 to 1:1.

[0018] Preferably, the solid content of the first active material layer slurry and the second active material layer slurry is independently 31% to 35%, the viscosity is independently 4000 mPa·s to 8000 mPa·s, and the fineness is independently ≤35 μm.

[0019] Preferably, the thickness ratio of the first active material layer to the second active material layer after drying is 1:1 to 1:9.

[0020] In a second aspect, the present invention provides a negative electrode sheet, which is prepared by the method for preparing a negative electrode sheet according to the first aspect.

[0021] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet described in the second aspect.

[0022] The numerical range described in the present invention not only includes the point values ​​listed above, but also includes any point values ​​between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values ​​included in the range.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention divides the negative electrode active material into two layers, an upper layer and an lower layer, and adopts silicon-carbon materials of different shapes in combination with different graphite materials to achieve different compaction densities. Among them, if the block silicon-carbon is subjected to greater pressure, it is easy to break, resulting in a decrease in capacity and cycle performance. Therefore, it is arranged in the first active material layer located in the upper layer. It has a lower compaction density and has the advantage of improving the rate performance of the battery. Spherical or quasi-spherical silicon-carbon particles can withstand greater pressure than block silicon-carbon and have a higher compaction density. Therefore, it is arranged in the second active material layer located in the lower layer. The advantage is that the capacity performance of the battery is improved.

[0025] 2. The blocky silicon carbon and fast-charging graphite in the first active material layer of the present invention are combined to give full play to the low internal resistance characteristics and further improve the battery rate performance. The spherical or quasi-spherical silicon carbon particles and high-capacity graphite in the second active material layer are combined to give full play to the high-capacity characteristics and further improve the capacity of the battery. Compared with the advantages of a single performance, the present invention can have both rate performance and capacity performance, which is more conducive to pursuing the comprehensive performance of the battery cell.

[0026] 3. The present invention also provides arc-shaped grooves on the negative electrode current collector for the spherical or quasi-spherical silicon-carbon particles in the second active material layer, which can improve the contact problem between the spherical or quasi-spherical silicon-carbon particles and the negative electrode current collector, and transform the point contact with the traditional current collector into surface contact with the arc-shaped grooves in the present invention, thereby increasing the peeling strength of the negative electrode pole piece, making it difficult for the negative electrode active material to fall off the negative electrode current collector, and extending the service life of the battery. DETAILED DESCRIPTION

[0027] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0028] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specific implementation methods are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the terms "including" and "having" in the description and claims of the present invention and any variations thereof are intended to cover non-exclusive inclusions.

[0029] In the description of the specific implementation methods of the present invention, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present invention, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0030] Reference to "embodiments" in the present invention means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present invention. The appearance of the phrase in various places in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described in the present invention may be combined with other embodiments.

[0031] In the description of the embodiments of the present invention, the term "and / or" is only a description of the association relationship of associated objects, indicating that three relationships may exist. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in the present invention generally indicates that the associated objects before and after are in an "or" relationship.

[0032] Throughout the present invention, numerical values ​​represent approximate measures or limits of ranges to cover minor deviations from given values ​​as well as embodiments with about the values ​​mentioned and embodiments with the exact values ​​mentioned. Except for the working examples provided at the end of the detailed description, all numerical values ​​of parameters (e.g., amounts or conditions) in this specification (including the appended claims) should be understood as modified by the term "about" in all cases, regardless of whether "about" actually appears before the numerical value. "About" indicates that the stated numerical value allows for some minor imprecision (close to the exact value of the value to some extent; approximately or reasonably close to the value; almost). If the imprecision provided by "about" is not otherwise understood in this ordinary sense in the art, "about" as used in the present invention at least indicates the variation that can be produced by the ordinary methods of measuring and using such parameters. For example, "about" may include a variation of less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5%, and in some aspects, optionally less than or equal to 0.1%.

[0033] Additionally, disclosure of ranges includes disclosure of all values ​​within the entire range and further divided ranges, including endpoints and sub-ranges given for such ranges.

[0034] In one embodiment of the present invention, a method for preparing a negative electrode sheet is provided, comprising:

[0035] S1. Preparing a negative electrode current collector, a first active material layer slurry and a second active material layer slurry;

[0036] S2. The second active material layer slurry is coated on the negative electrode current collector to form a second active material layer;

[0037] S3. The first active material layer slurry is coated on the second active material layer to form a first active material layer to obtain a negative electrode sheet to be processed;

[0038] S4. The negative electrode sheet to be processed is dried to form a negative electrode sheet;

[0039] The negative electrode current collector is provided with an arc-shaped groove, the first active material layer slurry includes block silicon carbon, the second active material layer slurry includes spherical or quasi-spherical silicon carbon particles, and the spherical or quasi-spherical silicon carbon particles are at least partially arranged in the arc-shaped groove.

[0040] Unlike conventional negative electrode active material layers that only use block silicon carbon or spherical or quasi-spherical silicon carbon particles, which can only achieve high rate performance or high capacity performance, the present invention divides the negative electrode active material layer into upper and lower layers, and uses block silicon carbon and spherical or quasi-spherical silicon carbon particles to obtain a battery with both capacity and rate performance, wherein block silicon carbon is easily broken due to pressure, resulting in a decrease in capacity and cycle performance, so it is arranged in the first active material layer located in the upper layer, and spherical or quasi-spherical silicon carbon particles can withstand greater pressure, so they are arranged in the second active material layer located in the lower layer, and at the same time, in conjunction with the above-mentioned double-layer structure, in order to solve the problem that the contact area between the traditional negative electrode current collector and the spherical or quasi-spherical silicon carbon particles is small, and they are easy to fall off from the negative electrode current collector during the battery charging and discharging process, the present invention also arranges an arc groove on the negative electrode current collector, which can increase the contact area between the spherical or quasi-spherical silicon carbon particles and the negative electrode current collector, reduce the contact internal resistance, and thus obtain a battery with high peel strength and both capacity and rate performance.

[0041] In one embodiment, the maximum depth of the arc-shaped groove is d, the opening diameter of the arc-shaped groove is D, the average particle size of the spherical or quasi-spherical silicon-carbon particles is D50, and the thickness of the negative electrode current collector is h, which satisfies the following relationship: , wherein 0<D≤D50, d<h / 2, α is a coefficient, 1≤α≤2.2, and α can be, for example, 1, 1.1, 1.2, 1.3, 1.5, 1.8, 2, 2.2, etc. The above values ​​are only examples and are not limiting.

[0042] In a preferred embodiment, the maximum depth of the arc-shaped groove is d, the opening diameter of the arc-shaped groove is D, the average particle size of the spherical or quasi-spherical silicon-carbon particles is D50, and the thickness of the negative electrode current collector is h, satisfying the following relationship: ;

[0043] Among them, 0<D≤D50, d<h / 2, α is a coefficient, 1≤α≤1.3.

[0044] The present invention changes the point contact between the traditional current collector and the spherical or quasi-spherical silicon-carbon particles into surface contact between the arc-shaped groove and the spherical or quasi-spherical silicon-carbon particles by arranging an arc-shaped groove on the negative electrode current collector, thereby increasing the contact area between the spherical or quasi-spherical silicon-carbon particles and the negative electrode current collector. At the same time, by limiting the relationship between the opening diameter of the arc-shaped groove and the particle size of the spherical or quasi-spherical silicon-carbon particles and the maximum depth of the arc-shaped groove, the spherical or quasi-spherical silicon-carbon particles are at least partially embedded in the arc-shaped groove, so that the spherical or quasi-spherical silicon-carbon particles can be better restrained by the arc-shaped groove, thereby further increasing the peeling strength of the negative electrode sheet.

[0045] In one embodiment, the first active material layer slurry further includes fast-filling graphite, and the total mass of the block silicon carbon and the fast-filling graphite accounts for 92.6% to 96.1% of the mass of the first active material layer.

[0046] In a preferred embodiment, the mass ratio of block silicon carbon to fast-filling graphite is 3:97-95:5.

[0047] It should be noted that fast-charging graphite is a graphite material used for fast charging. Compared with traditional conventional graphite, fast-charging graphite has a more uniform crystal structure and fewer crystal defects, which enables it to transmit lithium ions faster during the charging process. It can cooperate with the blocky silicon carbon in the first active material layer to give full play to its low internal resistance characteristics, further improve the fast charging performance of the battery, and thus significantly increase the charging speed.

[0048] Specifically, the total mass of bulk silicon carbon and fast-filling graphite in the first active material layer may account for 92.6%, 92.8%, 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, 95%, 95.2%, 95.5%, 95.8%, 96%, 96.1%, etc. The mass ratio of bulk silicon carbon and fast-filling graphite may be 3:97, 25:75, 55:45, 75:25, 95:5, etc. The above values ​​are for example only and are not limiting.

[0049] In one embodiment, the second active material layer slurry further includes high-capacity graphite, and the total mass of the spherical or quasi-spherical silicon-carbon particles and the high-capacity graphite accounts for 89.4% to 95.6% of the mass of the second active material layer.

[0050] In a preferred embodiment, the mass ratio of the spherical or quasi-spherical silicon-carbon particles to the high-capacity graphite is 3:97 to 1:1.

[0051] It should be noted that high-capacity graphite refers to graphite materials with high specific capacity and high energy density. High-capacity graphite materials can store more energy in battery applications and can be combined with spherical or quasi-spherical silicon carbon in the second active material layer to give full play to its high-capacity characteristics and further improve the capacity of the battery.

[0052] Specifically, the total mass of spherical or quasi-spherical silicon-carbon particles and high-capacity graphite accounts for 89.4%, 89.8%, 90%, 90.2%, 90.5%, 90.8%, 91%, 91.2%, 91.5%, 91.8%, 92%, 92.2%, 92.5%, 92.8%, 93%, 93.2%, 93.5%, 93.8%, 94%, 94.2%, 94.5%, 94.8%, 95%, 95.2%, 95.6%, etc. The mass ratio of spherical or quasi-spherical silicon-carbon particles to high-capacity graphite can be 3:97, 23:77, 43:57, 1:1, etc. The above values ​​are only examples and are not limited.

[0053] In one embodiment, the first active material layer and the second active material layer both include a conductive agent and a binder.

[0054] It is understandable that the present invention does not specifically limit the type of conductive agent, and the first active material layer and the second active material layer may select the same conductive agent or different conductive agents. Exemplary, it includes at least one of carbon-based materials, powdered nickel or other metal particles or conductive polymers. For example, natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, channel black, acetylene black, carbon nanotubes, carbon nanofibers, polyaniline, polythiophene, polyacetylene, polypyrrole, poly (3,4-ethylenedioxythiophene) polystyrene sulfonate, etc.

[0055] It is understandable that the present invention does not specifically limit the type of binder. Without violating the general concept of the present invention, the binder that can bond and maintain the negative electrode active material, enhance the contact between the negative electrode active material and the negative electrode conductor and the negative electrode active material and the negative electrode current collector, thereby stabilizing the structure of the negative electrode sheet is within the protection scope of the present invention. Exemplary, it contains thermoplastic resin or thermosetting resin. For example, polytetrafluoroethylene (PTFE), sodium carboxymethyl cellulose (CMC), styrene butadiene rubber (SBR), polyvinylidene fluoride (PVDF), nitrile rubber (NBR), styrene ethylene butylene styrene copolymer (SEBS), styrene butadiene styrene copolymer (SBS), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), sodium alginate, lithium alginate, etc.

[0056] In a preferred embodiment, the binders in the first active material layer and the second active material layer both include SBR, wherein the SBR content in the second active material layer is higher than the SBR content in the first active material layer.

[0057] The SBR content in the second active material layer is higher than that in the first active material layer. Therefore, during the coating of the electrode and subsequent baking, the SBR in the second active material layer migrates with the flow of the solvent and fills the gaps between the blocky silicon carbon and fast-charging graphite particles in the first active material layer, thereby ensuring the rapid and continuous conduction of lithium ions and further improving battery performance.

[0058] In one embodiment, the solid content of the first active material layer slurry and the second active material layer slurry is independently 31% to 35%, the viscosity is independently 4000 mPa·s to 8000 mPa·s, and the fineness is independently ≤35 μm.

[0059] Too high or too low solid content of the negative electrode active material layer slurry may lead to uneven electrode structure. Setting the solid content of the negative electrode active material layer slurry within the above range can make the negative electrode active material evenly distributed, forming a good conductive network, which is beneficial to improving the charging and discharging efficiency of the battery.

[0060] If the viscosity of the negative electrode active material slurry is too high, its leveling and wettability are poor, coating is difficult, and the surface of the electrode after drying is prone to cracking and the surface of the electrode is uneven, affecting the electrochemical performance of the battery. If the viscosity of the negative electrode active material layer slurry is too low, its stability is low, and the solid matter will agglomerate during the drying process, increasing the internal stress of the electrode, causing cracks in the electrode during rolling, which in turn affects the battery rate performance and cycle stability. Setting the viscosity of the negative electrode active material layer slurry within the above range can ensure the stability of the negative electrode slurry and reduce problems during the coating process.

[0061] The fineness of the negative electrode active material slurry is an important performance indicator of the battery slurry. It has a great influence on the surface quality and uniformity of the formed coating and the storage stability of the slurry. Setting the fineness of the negative electrode active material layer slurry within the above range can better wet the solid particles and make the surface of the prepared active material layer uniform and smooth without vertical scratches.

[0062] In one embodiment, the thickness ratio of the first active material layer to the second active material layer after drying is 1:1 to 1:9.

[0063] The first active material layer includes block silicon carbon and fast-charging graphite, and its advantage lies in fast-charging performance, while the second active material layer includes spherical or quasi-spherical silicon carbon particles and high-capacity graphite, and its advantage lies in capacity performance. The compaction density of the first active material layer is relatively low, and lithium ions can preferentially and quickly pass through the first active material layer structure and then through the second active material layer. In this way, the negative electrode sheet forms an overall structure with both rate performance and capacity performance. The thickness ratio of the first active material layer and the second active material layer after drying is within the above range, which can ensure that the battery has good capacity performance while having certain rate performance.

[0064] Specifically, the thickness ratio of the first active material layer to the second active material layer after drying may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc. The above values ​​are only examples and are not limiting.

[0065] The present invention also provides a lithium ion battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte. The contents related to the negative electrode sheet can be referred to the above introduction, and will not be repeated here.

[0066] In one embodiment, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer covering the surface of the positive electrode current collector, and the positive electrode active material layer includes a positive electrode active material, a binder and a conductive agent.

[0067] It is understood that the present invention has no particular restrictions on the positive electrode current collector material, as long as it has conductivity and does not cause chemical changes in the battery. Exemplarily, the positive electrode current collector includes but is not limited to any one of aluminum, nickel or stainless steel, such as the positive electrode current collector is aluminum foil.

[0068] It is to be understood that the present invention has no particular limitation on the shape of the positive electrode current collector. Exemplarily, the shape of the positive electrode current collector includes but is not limited to metal foil, metal grid, metal mesh, metal foam, and the like.

[0069] It is understood that the positive electrode active material is a compound that reversibly intercalates and deintercalates lithium, and the positive electrode active material in the present invention can be any positive electrode active material known in the art. Exemplarily, the positive electrode active material can be selected from lithium cobalt oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium iron manganese phosphate, lithium vanadium phosphate, lithium vanadium phosphate, lithium iron phosphate, lithium titanate or lithium-rich manganese elastic-based materials, etc.

[0070] In order to prevent short circuits inside the battery, lithium-ion batteries also need to include a diaphragm, which is located between the positive electrode plate and the negative electrode plate to block the transmission of electrons inside the battery. The diaphragm in the present invention is any one of the various diaphragms used in lithium-ion batteries, and the diaphragm includes a material with low resistance to ion migration of electrolytes and good electrolyte retention ability. In an embodiment of the present invention, the diaphragm includes but is not limited to one or more of polypropylene, polyethylene, polyvinylidene fluoride, polyimide, and polyacrylonitrile. Users can choose according to actual needs, and no specific restrictions are made here. It should be noted here that when a solid electrolyte is used, the solid electrolyte acts as a diaphragm or is coated on the diaphragm, and a conventional diaphragm is no longer needed.

[0071] The electrolyte includes a liquid electrolyte and a solid electrolyte. The liquid electrolyte includes a lithium salt and a non-aqueous solvent, and the lithium salt includes one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, Li2SiF6, LiBOB or LiBF2(C2O4). Users can choose according to actual needs, and no specific restrictions are made here. In the embodiment of the present invention, the lithium salt is preferably LiPF6, because LiPF6 can have high ionic conductivity and can improve the cycle characteristics of the battery.

[0072] The non-aqueous solvent includes one or more of carbonate compounds, carboxylate compounds, and ether compounds. Further, the carbonate compounds include linear carbonate compounds, cyclic carbonate compounds, and fluorinated carbonate compounds. Specifically, the chain carbonate compounds include but are not limited to diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methylpropyl carbonate (MPC), ethylpropyl carbonate (EPC) or ethylmethyl carbonate (MEC), etc.; the cyclic carbonate compounds include but are not limited to ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC) or vinylethylene carbonate (VEC), etc.; the fluorinated carbonate compounds include but are not limited to fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate or trifluoromethylethylene carbonate, etc.

[0073] The carboxylate compounds include, but are not limited to, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, γ-butyrolactone, decanoic acid lactone, valerolactone, mevalonolactone, caprolactone or methyl formate.

[0074] The ether compound includes, but is not limited to, dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran or tetrahydrofuran, and the like.

[0075] Furthermore, the non-aqueous solvent may also include one or more of dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate or phosphate ester.

[0076] In the embodiment of the present invention, the solid electrolyte includes but is not limited to a polymer solid electrolyte, an oxide solid electrolyte, a sulfide solid electrolyte, and the like.

[0077] In specific applications, the sulfide solid electrolyte can be selected from: Li2S-P2S5, Li2S-P2S5-MS x (where M is Si, Ge and Sn and 0≤x≤2), Li 3.4 Si 0.4 P 0.6 S4, Li 10 GeP2S 11.7 O 0.3 , Li 9.6 P3S 12 、Li7P3S 11 、Li9P3S9O3、Li 10.35 Si 1.35 P 1.65 S 12 , Li 9.81 Sn 0.81 P 2.19 S 12 , Li 10 (Si 0.5 Ge 0.5 )P2S 12 、Li(Ge 0.5 Sn 0.5 )P2S 12 、Li(Si 0.5 Sn 0.5 )P2S 12 , Li 10 GeP2S 12 (LGPS), Li6PS5X (where X is Cl, Br or I), Li7P2S8I, Li 10.35 Ge 1.35 P 1.65 S 12 , Li 3.25 Ge0.25 P 0.75 S4, Li 10 SnP2S 12 , Li 10 SiP2S 12 , Li 9.54 Si 1.74 P 1.44 S 11.7 C l0.3 or (1 - x)P2S 5-x Li2S (where 0.5 ≤ x ≤ 0.7) or at least one of them.

[0078] In specific applications, the halide solid electrolyte can be selected from: Li2CdC l4 , Li2MgC l4 , Li2Cd I4 , Li2ZnI4, Li3OCl, LiI, Li5ZnI4 or Li3OCl 1-x Br x (where 0 < x < 1) or at least one of them.

[0079] In specific applications, the oxide solid electrolyte can be selected from: perovskite type, garnet type, LISICON type, NASICON type, among which, the perovskite type solid electrolyte material is preferably LLTO (lithium lanthanum titanate, Li 0.33 La 0.56 TiO3), the garnet type solid electrolyte material is preferably LLZO (lithium lanthanum zirconate, Li7La3Zr2O 12 ), NASICON (sodium superionic conductor) type solid electrolyte material is preferably LATP (lithium aluminum titanium phosphate, Li 1.3 Al 0.3 Ti 1.7 (PO4)3) or at least one of them.

[0080] The embodiments of the present invention will be described more specifically below through examples. However, the embodiments of the present invention are not limited to these examples only.

[0081] Example 1

[0082] 1. Preparation of the negative electrode sheet

[0083] (1) Preparation of the negative electrode current collector:

[0084] The negative electrode current collector uses copper foil, and a plurality of arc-shaped grooves are opened on both sides of the negative electrode current collector. Among them, the thickness h of the negative electrode current collector is 6 μm; the particle size D50 of the spherical or quasi-spherical silicon-carbon particles is 6 μm, and the opening diameter D of the arc-shaped groove is 4.8 μm; the vertical distance from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove , in this embodiment, d=1.2μm;

[0085] Substituting the above data into the formula, we get:

[0086] , =1, falling within the range of 1≤α≤2.2.

[0087] (2) Preparation of negative electrode active material layer slurry:

[0088] Based on the total mass of block silicon carbon & fast-filling graphite, Super P, SWCNTs, MWCNTs, PPA, SBR and CMC, block silicon carbon & fast-filling graphite, Super P, SWCNTs, MWCNTs, PPA, SBR and CMC are prepared in a ratio of 92.6%: 0.5%: 0.1%: 0.1%: 1.5%: 2.0%: 3.2% (mass percentage) to prepare a first active material layer slurry, wherein the mass ratio of block silicon carbon and fast-filling graphite is 20:80, the solid content of the first active material layer slurry is 33%, the viscosity is 5000 mPa·s, and the fineness is 35 μm;

[0089] Based on the total mass of spherical or quasi-spherical silicon-carbon particles & high-capacity graphite, Super P, SWCNTs, MWCNTs, PPA, SBR and CMC, the second active material layer slurry is prepared with spherical or quasi-spherical silicon-carbon particles & high-capacity graphite, Super P, SWCNTs, MWCNTs, PPA, SBR and CMC in a mass ratio of 89.4%:1.0%:0.2%:0.2%:1.5%:3.0%:4.7% (mass percentage), wherein the mass ratio of spherical or quasi-spherical silicon-carbon particles to high-capacity graphite is 20:80, the solid content of the second active material layer slurry is 34%, the viscosity is 6000 mPa·s, and the fineness is 33 μm.

[0090] (3) Preparation of negative electrode sheet:

[0091] The prepared second active material layer slurry is first coated on the surface of the negative electrode current collector by a double-layer coating die head of a coating machine, thereby forming a second active material layer on the surface of the negative electrode current collector, and then the first active material layer slurry is coated on the surface of the second active material layer, thereby forming a first active material layer on the surface of the second active material layer, and baking is performed to obtain a high energy density and low resistance battery negative electrode sheet. After baking, the thickness ratio of the first active material layer to the second active material layer is 3:7, and the double-sided surface density is controlled to be 200g / m 2 The compaction density of the first active material layer after baking is 1.2 g / m 3 The compaction density of the second active material layer is 1.4 g / m 3.

[0092] 2. Preparation of positive electrode

[0093] LiNi 0.9 Co 0.05 Mn 0.05 The total mass of O2, SWCNTs, MWCNTs and PVDF was used as the basis. 0.9 Co 0.05 Mn 0.05 O2, SWCNTs, MWCNTs and PVDF were prepared into positive electrode slurry in the proportion of 98.1%:0.1%:0.6%:1.2% by mass, wherein the positive electrode slurry had a solid content of 66%, a viscosity of 6200 mPa·s, and a fineness of 30 μm. The positive electrode sheet was baked to control the double-sided surface density to 550 g / m 2 The compaction density of the positive electrode active material layer after baking is 3.45g / m 3 .

[0094] 3. Cell Preparation

[0095] The positive and negative electrode sheets are stacked, baked, injected, formed and divided into different capacity to produce a battery cell with a capacity of 27Ah.

[0096] Example 2

[0097] The difference between this embodiment and embodiment 1 is that the thickness h of the negative electrode current collector is 8 μm; the opening diameter D of the arc-shaped groove is 6 μm; the particle size D50 of the spherical or quasi-spherical silicon-carbon particles is 7.5 μm; the vertical distance d from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove is, , in this embodiment, d=1.5μm;

[0098] Substituting the above data into the formula, we get:

[0099] , =1, falling within the range of 1≤α≤2.2;

[0100] In the negative electrode first active material layer slurry, the mass proportion of each component is: block silicon carbon & fast charging graphite: SuperP: SWCNTs: MWCNTs: PPA: SBR: CMC = 95.3%: 0.5%: 0.1%: 0.1%: 1.5%: 2.0%: 0.5%;

[0101] In the negative electrode second active material layer slurry, the mass proportion of each component is: spherical or quasi-spherical silicon carbon & high-capacity graphite: Super P: SWCNTs: MWCNTs: PPA: SBR: CMC = 93.6%: 1.0%: 0.2%: 0.2%: 1.5%: 3.0%: 0.5%;

[0102] The rest of the preparation methods and parameters were consistent with those in Example 1.

[0103] Example 3

[0104] The difference between this embodiment and embodiment 1 is that the thickness h of the negative electrode current collector is 9 μm; the opening diameter D of the arc-shaped groove is 8.4 μm; the particle size D50 of the spherical or quasi-spherical silicon carbon particles is 14 μm; the vertical distance d from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove is,

[0105] , in this embodiment, d=1.4μm;

[0106] Substituting the above data into the formula, we get:

[0107] , =1, falling within the range of 1≤α≤2.2;

[0108] In the negative electrode first active material layer slurry, the mass proportion of each component is: block silicon carbon & fast charging graphite: SuperP: SWCNTs: MWCNTs: PPA: SBR: CMC = 96.1%: 0.5%: 0.1%: 0.1%: 0.7%: 2.0%: 0.5%;

[0109] In the negative electrode second active material layer slurry, the mass proportion of each component is: spherical or quasi-spherical silicon carbon & high-capacity graphite: Super P: SWCNTs: MWCNTs: PPA: SBR: CMC = 95.6%: 0.5%: 0.1%: 0.1%: 0.2%: 3.0%: 0.5%;

[0110] The rest of the preparation methods and parameters were consistent with those in Example 1.

[0111] Example 4

[0112] The only difference between this embodiment and embodiment 1 is that the vertical distance d from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove is 0.4 μm, and the other preparation methods and parameters are consistent with those of embodiment 1;

[0113] Substituting the above data into the formula, we get:

[0114] , ≈0.3, which does not fall within the range of 1≤α≤2.2.

[0115] Example 5

[0116] The only difference between this embodiment and embodiment 2 is that the vertical distance d from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove is 0.5 μm, and the rest of the preparation methods and parameters are the same as those of embodiment 2;

[0117] Substituting the above data into the formula, we get:

[0118] , ≈0.3, which does not fall within the range of 1≤α≤2.2.

[0119] Example 6

[0120] The only difference between this embodiment and embodiment 3 is that the vertical distance d from the plane where the opening of the arc-shaped groove is located to the deepest part of the bottom surface of the arc-shaped groove is 0.6 μm, and the rest of the preparation methods and parameters are the same as those of embodiment 3;

[0121] Substituting the above data into the formula, we get:

[0122] , ≈0.4, which does not fall within the range of 1≤α≤2.2.

[0123] Comparative Example 1

[0124] The difference between this comparative example and Example 1 is that the negative electrode current collector does not have an arc-shaped groove, and the other preparation methods and parameters are consistent with those of Example 1.

[0125] Comparative Example 2

[0126] The difference between this comparative example and Example 2 is that the negative electrode current collector does not have an arc-shaped groove, and the other preparation methods and parameters are consistent with those of Example 2.

[0127] Comparative Example 3

[0128] The difference between this comparative example and Example 3 is that the negative electrode current collector does not have an arc-shaped groove, and the other preparation methods and parameters are consistent with Example 3.

[0129] Comparative Example 4

[0130] The difference between this comparative example and Example 1 is that the spherical or quasi-spherical silicon carbon & high-capacity graphite in the second active material layer of the negative electrode is replaced with block silicon carbon & fast-charging graphite with an equal mass ratio, and the rest of the preparation methods and parameters are consistent with Example 1.

[0131] Comparative Example 5

[0132] The difference between this comparative example and Example 1 is that the blocky silicon carbon & fast-charging graphite in the first active material layer of the negative electrode is replaced with spherical or quasi-spherical silicon carbon & high-capacity graphite of equal mass proportion, and the rest of the preparation methods and parameters are consistent with Example 1.

[0133] Comparative Example 6

[0134] The difference between this comparative example and Example 2 is that the spherical or quasi-spherical silicon carbon & high-capacity graphite in the second active material layer of the negative electrode is replaced with block silicon carbon & fast-charging graphite with an equal mass ratio, and the rest is the same as Example 2.

[0135] Comparative Example 7

[0136] The difference between this comparative example and Example 2 is that the blocky silicon carbon & fast-charging graphite in the first active material layer of the negative electrode is replaced with spherical or quasi-spherical silicon carbon & high-capacity graphite of equal mass proportion, and the rest is the same as Example 2.

[0137] Comparative Example 8

[0138] The difference between this comparative example and Example 3 is that the spherical or quasi-spherical silicon carbon & high-capacity graphite in the second active material layer of the negative electrode is replaced with block silicon carbon & fast-charging graphite with an equal mass ratio, and the rest is the same as Example 3.

[0139] Comparative Example 9

[0140] The difference between this comparative example and Example 3 is that the blocky silicon carbon & fast-charging graphite in the first active material layer of the negative electrode is replaced with spherical or quasi-spherical silicon carbon & high-capacity graphite of equal mass proportion, and the rest is the same as Example 3.

[0141] Test conditions

[0142] The performance test of the batteries in the above embodiments and comparative examples was carried out, and the test conditions were as follows:

[0143] (1) Peel strength test method:

[0144] Prepare test samples that meet the requirements. First, use a flat paper cutter to cut the negative electrode sheet into strips with a length of 150 mm and a width of 25 mm. Then use dust-free paper to wipe the scaleless steel ruler clean without leaving stains and dust. Secondly, stick a double-sided tape with a width of 25 mm on the scaleless steel ruler, with a length of 70 mm and a center position. Then stick the negative electrode sheet on the double-sided tape with the end faces flush. Use a pressure wheel (2 kg) with a diameter of 84 mm and a height of 45 mm to roll back and forth on the surface of the negative electrode sheet 3 times. After the free end of the negative electrode sheet is folded 180°, it is clamped on the upper fixture of the tensile tester, and a scaleless steel ruler is clamped on the lower clamp. Under the conditions of 22℃~28℃ and humidity less than 25%, several 25mm wide negative electrode sheets are prepared. The stretching speed of the negative electrode sheet is 100mm / min. The test takes the average value of the stretching of 25mm~80mm (total stretching distance of 100mm), and the negative electrode sheet is peeled off. When the negative current collector and the negative active material layer are completely separated, the test result of the peeling strength is read.

[0145] (2) Discharge capacity test method:

[0146] At room temperature, use a constant current charge of 0.33C to 4.3V, and a constant voltage charge of 4.3V until the current drops to 0.05C. After standing for 10 minutes, discharge at a rate of 0.33C to 2.5V. The above charge and discharge conditions are cycled 3 times, and the average of the 3 discharge capacities is taken as the actual capacity of a single battery cell. Test five batteries and take the average capacity of the five batteries. During the test, put on the clamping plate, and the torque of the clamping plate is 1.8N·m.

[0147] (3) Rate performance test method:

[0148] At room temperature, based on the above 0.33C rate test capacity, use 0.33C rate constant current charge to 4.3V, 4.3V constant voltage charge until the current drops to 0.05C rate, stand for 90 minutes, and then use 0.33C / 0.5C / 1C / 2C different rates to discharge to 2.5V. Test five batteries and take the average capacity of the five batteries. During the test, put on the clamping plate, and fix the clamping plate with a torque of 1.8N·m.

[0149] The test results are shown in Table 1:

[0150] Table 1

[0151]

[0152] According to the above table, it can be seen from the comparison between Examples 1 to 3 and Comparative Examples 4 to 9 that when the negative electrode active material layer is only a single-shaped silicon-carbon material with a graphite material, it can only exert high capacity or high rate performance. The advantage of a single performance does not meet the demand for comprehensive design of the battery cell. The present invention designs the negative electrode active material layer into a double-layer structure according to the characteristics of silicon-carbon materials of different shapes, and matches different graphite materials to obtain a negative electrode sheet with high peel strength and both capacity performance and rate performance. From Comparative Example 3, it can be seen that the arc-shaped grooves set in the layered structure of the present invention increase the contact area between the spherical or quasi-spherical silicon-carbon particles in the second active material layer and the negative electrode current collector, thereby increasing the peel strength of the negative electrode, and by limiting the relationship between the opening diameter of the arc-shaped grooves and the average particle size of the spherical or quasi-spherical silicon-carbon particles and the maximum depth of the arc-shaped grooves, the spherical or quasi-spherical silicon-carbon particles are at least partially embedded in the arc-shaped grooves and can be better restrained by the arc-shaped grooves, thereby further increasing the peel strength of the negative electrode sheet and improving the overall performance of the battery.

[0153] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a negative electrode sheet, characterized in that: include: S1. Preparing a negative electrode current collector, a first active material layer slurry and a second active material layer slurry; S2. The second active material layer slurry is coated on the negative electrode current collector to form a second active material layer; S3. coating the first active material layer slurry on the second active material layer to form a first active material layer to obtain a negative electrode sheet to be processed; S4. The negative electrode sheet to be processed is dried to form a negative electrode sheet; The negative electrode current collector is provided with an arc-shaped groove, the first active material layer slurry includes block silicon carbon, the second active material layer slurry includes spherical or quasi-spherical silicon carbon particles, and the spherical or quasi-spherical silicon carbon particles are at least partially arranged in the arc-shaped groove; The maximum depth of the arc-shaped groove is d, the opening diameter of the arc-shaped groove is D, the average particle size of the spherical or quasi-spherical silicon-carbon particles is D50, and the thickness of the negative electrode current collector is h, which satisfies the following relationship: , where 0<D≤D50, d<h / 2, α is the coefficient, 1≤α≤2.

2.

2. The method for preparing a negative electrode sheet according to claim 1, characterized in that: The first active material layer slurry also includes fast-filling graphite, and the total mass of the blocky silicon carbon and the fast-filling graphite accounts for 92.6% to 96.1% of the mass of the first active material layer.

3. The method for preparing a negative electrode sheet according to claim 1, characterized in that: The second active material layer slurry further includes high-capacity graphite, and the total mass of the spherical or quasi-spherical silicon-carbon particles and the high-capacity graphite accounts for 89.4% to 95.6% of the mass of the second active material layer.

4. The method for preparing a negative electrode sheet according to claim 2, characterized in that: The mass ratio of the block silicon carbon to the fast-filling graphite is 3:97 to 95:

5.

5. The method for preparing a negative electrode sheet according to claim 3, characterized in that: The mass ratio of the spherical or quasi-spherical silicon-carbon particles to the high-capacity graphite is 3:97 to 1:

1.

6. The method for preparing a negative electrode sheet according to claim 1, characterized in that: The solid content of the first active material layer slurry and the second active material layer slurry are each independently 31% to 35%, the viscosity is each independently 4000 mPa·s to 8000 mPa·s, and the fineness is each independently ≤35 μm.

7. The method for preparing a negative electrode sheet according to claim 1, characterized in that: The thickness ratio of the first active material layer to the second active material layer after drying is 1:1 to 1:

9.

8. A negative electrode plate, characterized in that: The negative electrode sheet is prepared by the method for preparing a negative electrode sheet according to any one of claims 1 to 7.

9. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the negative electrode sheet is the negative electrode sheet according to claim 8.

Citation Information

Patent Citations

  • Negative pole piece and lithium ion secondary battery thereof

    CN111490253A

  • Negative plate and lithium ion battery comprising the same

    CN112563453A

  • Lithium ion battery negative electrode with high conductivity and high stability

    CN117497705A

  • Composite negative plate, preparation method thereof and lithium ion battery

    CN117810358A